Condicionantes morfoestruturais na evolução da paisagem no oeste do Paraná e suas interações com os latossolos vermelhos - Silva, Bruno Aparecido da (2021)
The evolution dynamic of the landscapes of the Basalt Plateau of the Paraná Sedimentary Basin remain little understood, especially regarding the influence of lithostructural, tectonic, and pedogeomorphic interaction. The hypotheses of this thesis propose that lithostructural factors acted in the differential control of relief dissection, as tectonic pulses interrupted the stability of the landscape during the Cenozoic. In addition, the evolution of the Ferralsols would be conditioned to this dynamic that contributed to the input of allochtonous parent material to the Ferralsols on more recent sectors of the landscape. Therefore, this thesis investigates the factors that acted on the elaboration of the relief and its forms, and on the genesis and evolution of Ferralsols found on the landscape of West Paraná, having the hydrographic basins of the São Francisco Verdadeiro and São Francisco Falso Rivers, left-hand tributaries of the Paraná River, as spatial outline. The methodology was based on the attainment of data in the field, office, and laboratory. In the field, a survey of tectonic structures was carried out, in addition to differentiation of the lithological members, identification of geomorphic surfaces, soil description and sample collection from six Ferralsols profiles for subsequent investigation of their physical, chemical, mineralogical, geochemical, and macro-micromorphological attributes. In the office, the structural data served as a basis for the elaboration of stereograms and for the analysis of paleostress. Cartographic products of the geology (lithostructure and faults), modelled types, elevation, knickpoint density, relief rugosity, swath profiles, and the spatialization of geomorphic surfaces were also elaborated. Morphometric techniques related to the longitudinal profile of the rivers, slope-length index, and basin asymmetry factor were used to demonstrate the tecto-lithostructural control on the geomorphic configuration of the studied river basins. In the laboratory, the physical, chemical, mineralogical, geochemical, and micromorphological attributes of the Ferralsols were investigated. From the statistical evaluation of Principal Components Analysis, it was possible to differentiate the Ferralsols into two main groups, while the macro and micromorphology indicated important evidence of allochtony in profiles P.1, P.3, and P.6. In general, the results enable identification of the lithostructural variations between the lithological members of the Serra Geral Group that outcrop in the study area, these being composed of massive tabular flood basalts and vesicular compounds, which controlled the uneven dissection of the relief, as well as the occurrence of strike-slip faults, mainly NW-SE and NE-SW, which directed the sculpting of the relief forms and the elaboration of the geomorphic surfaces. Two tectonic pulses were recorded that reactivated the transcurrent faults (NE-SW, NW-SE, N-S and E-W) and dismantled the pre-Neogene, geomorphic surface S1, and contributed to the elaboration of surfaces S4 and S5, during the Quartenary. These pulses appear to have been decisive for interrupting the evolution of the Ferralsols and partially removing the most varied weathering profiles, generating allochtonous material for the transitional (P.3) and more subsided sectors of the landscape (P.1 and P.6), where less weathered Ferralsols developed. It has been demonstrated that, in addition to climatic influence, there was an overlap of lithostructural and tectonic controls on the evolution of the regional landscape, which triggered important geomorphic processes of base level change, processes of etching/stripping, and slope retreat in the studied basins. Furthermore, the results enable the conclusion that the evolution of Ferralsols was conditioned to the polygenetic dynamic of the landscape, reflecting in soils developed from autochtonous parent materials (P.2, P.4, and P.5) and allochtonous parent materials (P.1, P.3 e P.6) over the five geomorphic surfaces identified in the basins of the São Francisco Verdadeiro and São Francisco Falso Rivers.